An aeronautical data communication demand model for the North Atlantic oceanic airspace - Hillebrecht, Alexander; Marks, Tobias; Gollnick, Volker (CEAS Aeronautical Journal, 2023)
Information exchange via aeronautical data communication is of increasing importance for the communication between pilots and air traffic control, providing the basis for surveillance of aircraft in oceanic or remote airspaces, as well as enabling the communication between an airlines’ fleet and its operational control. The aeronautical data communication that is being transmitted via data link encompasses, among others, surveillance-related aircraft position updates, clearances for flight path change requests, maintenance-related status reports, estimated arrival times and weather information in accordance with the required performance, that is set by technical standards. Aeronautical data communication events are driven by an aircraft’s flight phase, the current airspace or may occur in a randomized manner throughout the flight. As the usage of aeronautical data communication is expected to grow in future, ample data link technologies are being evaluated and developed. The usability and operational value of new data link technologies for aeronautical applications can be evaluated by applying suitable models of the respective data link communication pattern combined with operational simulations. Current models for aeronautical data communication demand support the design and evaluation of direct aircraft-to-ground communication networks. The geographical location of the data communication demand is secondary for these models, since coverage areas can be defined, where direct communication links are available. New data link technologies offer the opportunity of direct data transfer between aircraft and forwarding of messages from sending aircraft to a ground entity via ad-hoc communication networks between aircraft. This is of special interest for the North Atlantic oceanic airspace, an airspace with high traffic density and little ground infrastructure, where communication currently relies mostly on satellite-based systems. For these airborne ad-hoc networks the definition of coverage areas around ground or ...